CONTROLE QUÃMICO DAS DOENÃ‡AS FOLIARES DO AMENDOIM (Arachis hypogaea L.) - Lopes, Maria Elizabete B. M.; Lasca, Dalmo H. C.; Guilhem, Dulcinei J.; Montes, SÃ´nia M. N. M.; CesÃ¡rio, Antonio C.; Ceravolo, Leonardo (REVISTA DE AGRICULTURA, 2015)
CONTROLE QUÃMICO DAS DOENÃ‡AS FOLIARES DO AMENDOIM (Arachis hypogaea L.)